PENGEMBANGAN E-LKPD BERBANTUAN APLIKASI LIVEWORKSHEET PADA MATA PELAJARAN BAHASA INGGRIS - Riyadi Saputra; Zumrotun Lutfiah; Seftika Andini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The background of this research is the discovery of problems in learning English,where students were less engaged in completing the worksheets provided by theteacher due to their monotonous and unattractive appearance. This study aims todevelop Electronic Student Worksheets (E-LKPD) assisted by the Liveworksheetsapplication for fourth-grade English subjects at SDN 01 Sitiung that are valid,practical, and effective to improve learning outcomes. This research employed theResearch and Development (R&D) method using the 4D development model,consisting of the stages of define, design, development, and disseminate. Thevalidation results indicated that the E-LKPD achieved a very good level offeasibility with content validation at 82.5%, language 96%, graphics 100%,teaching module 80%, and questions 82.8%. The practicality test showed anaverage score of 96.3% from teachers and 94% from students, indicating that theE-LKPD is highly practical to use. The findings revealed that the Liveworksheets-assisted E-LKPD can facilitate teachers, enhance students learning motivation,and help students understand English materials interactively.